Economic valuation of preventing fatal and serious road injuries. Results of a Willingness-To-Pay study in four European countries. (August 2022) - Schoeters, Annelies; Large, Maxime; Koning, Martin; Carnis, Laurent; Daniels, Stijn; Mignot, Dominique; Urmeew, Raschid; Wijnen, Wim; Bijleveld, Frits; van der Horst, Martijn
Highlights: The Value of a Statistical Life in road safety is estimated at 6.2 Million EUR. Avoiding a road fatality is valued 7 times higher than avoiding a serious injury. Human costs of road victims are valued higher in Germany than in France. Abstract: This paper presents the results of a stated choice study for estimating the Willingness-To-Pay of respondents in four European countries (Belgium, France, Germany and the Netherlands) to reduce the risk of fatal and serious injuries in road crashes. Respondents were confronted with hypothetical route choices that differ in respect of travel costs, travel time and crash risk. The survey was completed by 8, 002 respondents, equally spread over the four participating countries and representative for each country with regards to gender, age and region. Possible biases caused by problematic choice behaviour such as inconsistent, irrational or lexicographic answers were addressed. The resulting values were estimated by means of a mixed logit model allowing to account for the panel nature of the data. The Value of a Statistical Life (VSL) was estimated at 6.2 Mill EUR, the Value of a Statistical Serious Injury (VSSI) at 950, 000 EUR, and the Value of Time (VoT) at 16.1 EUR/h. Consequently, the relative value of avoiding a fatal injury is estimated to be around 7 times higher than the value of an avoided serious injury. The study revealed differences between countries with France showing values that are significantly lower than the average and Germany showing values that are significantly higher. The estimated VSL values are considerably higher than the values currently used in the four countries, but they are within the range of values found in similar stated choice studies. The results can be used as an input in a broad range of socioeconomic studies including cost-benefit analysis and assessments of socioeconomic costs of road crashes.